Brown, Michelle P. 2023. Bede and the Theory of Everything. London: Reaktion Books. Pp. 312. ISBN 9781789147889. - Christine Rauer (SELIM, 2024)
Book review of Brown, Michelle P. 2023. Bede and the Theory of Everything. London: Reaktion Books. Pp. 312. ISBN 9781789147889.